2007
DOI: 10.1007/s10973-006-7915-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetry as a screening tool for the estimation of the vapor pressures of pure compounds

Abstract: A simplified approach was developed to estimate the vapor pressure of pure compounds from experimental data obtained by isothermal thermogravimetric (TG) analysis. A numerical procedure was developed to estimate the Antoine parameters of the substance by the analysis of isothermal TG data. The results of the experimental validations carried out evidenced that at least a preliminary estimation of vapour pressures of pure substances by the analysis of TG data is possible. The limited time and the reduced amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The vapour pressures omitted were in good agreement (except for [16]) with our previous transpiration result [4]. But it has turned out that new vapour pressures measured by static method recently [14] were slightly higher (see figure S1) in comparison to our published transpiration results [4].…”
Section: Vapour Pressures Of 13-propanediolsupporting
confidence: 84%
See 1 more Smart Citation
“…The vapour pressures omitted were in good agreement (except for [16]) with our previous transpiration result [4]. But it has turned out that new vapour pressures measured by static method recently [14] were slightly higher (see figure S1) in comparison to our published transpiration results [4].…”
Section: Vapour Pressures Of 13-propanediolsupporting
confidence: 84%
“…In the meantime, an extended GC-correlation study of a,x-alkanediols was published by Chickos et al [13], as well as a very careful vapour pressure measurements were reported from the static method just recently [14]. We also overlooked in reference [4] vapour pressures measured by ebulliometry [15] and by the thermogravimetry [16].…”
Section: Vapour Pressures Of 13-propanediolmentioning
confidence: 99%
“…In this work, the suitability of the conventional TGA method for measuring the total vapor pressure of several hydrophobic DESs was analyzed. First, the values of k (assumed to be constant for all materials in previous works ,, ) for the pure components ethylene glycol, glycerol, decanoic acid, and thymol were determined using the TGA method. Ethylene glycol and glycerol were chosen to confirm the reproducibility of our results with previous literature, while decanoic acid and thymol were selected as the reference substances of known vapor pressure used in this work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The most common screening method for total vapor pressure measurement is the use of a thermogravimetric analyzer (TGA), which has been used to investigate the vapor pressure of liquids as well as the sublimation pressure of solids. This method has also been used for assessment of the total vapor pressure of many ILs and a few hydrophilic DESs. Another method for measuring vapor pressure data is the Knudsen method, which has also been used before to measure the total vapor pressure of a few ILs and hydrophilic DESs. , A disadvantage of both methods is that only the total vapor pressure of the DES (i.e., a binary mixture) is measured and not the two partial vapor pressures of the DES constituents separately .…”
Section: Introductionmentioning
confidence: 99%